Testing the key processes that accelerate outer radiation belt relativistic electrons during geomagnetic storms - Hua, Man; Bortnik, Jacob; Spence, Harlan E.; Reeves, Geoffrey D. (Frontiers in Astronomy and Space Sciences, 2023)
Since the discovery of the Earth’s radiation belts in 1958, it has always been a challenge to determine the dominant physical mechanisms, whether local acceleration by chorus or inward radial diffusion, that leads to outer radiation belt relativistic electron flux enhancements. In this study, we test a chain of processes with several potential successive steps that is believed to accelerate outer belt relativistic electrons. By performing correlation analysis of different part of this chain, including the geomagnetic condition, evolution of source and seed electron fluxes, chorus wave activity, and maximum fluxes (jmax) of relativistic electrons, we aim to identify the critical steps that lead to acceleration of MeV electrons. Based on 5-years of Van Allen Probes observations, our results confirm the repeatable response of both source and seed electrons to the storms, showing a significant flux enhancement during the main phase of storms, followed by either a gradual decay or flux persistence at a stable level. However, it is the intense and prolonged occurrence of substorms that contributes to the long-lasting existence of both source and seed electrons, which is also strongly associated with the jmax of relativistic electrons. The significant correlation (Correlation Coefficient, CC~0.8) between the seed electron fluxes and jmax reveal that the prolonged and pronounced seed electrons are the prerequisite for the significant flux enhancement of relativistic electrons regardless of the acceleration mechanism. The slightly smaller CC (~0.5-0.7) between source electron fluxes and jmax of relativistic electrons indicates that while local acceleration by chorus wave plays an important role to accelerate relativistic electrons to jmax, other mechanisms such as inward radial diffusion are still needed in this process. The CC between the source electrons and the chorus wave amplitude increases with increasing levels of substorms, showing (CC)max of ~0.8, which further supports the crucial role of chorus waves in accelerating the relativistic electrons during intense